2006
DOI: 10.1002/ajmg.a.31222
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in an adult with 6p25 deletion syndrome

Abstract: Chromosomal deletions at 6p25-p24 are rare findings in patients with developmental delay. There is limited information about the adult phenotype. We present a 36-year-old patient with schizophrenia, mild mental retardation, progressive hearing deficits, and characteristic facial features. Ocular (Axenfeld-Rieger anomaly) abnormalities were diagnosed in infancy; vision, however, has remained unimpaired. There were no other major congenital anomalies. Brain imaging showed only minor changes. There was no family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Furthermore, brain MRI in Patient 4 at 28 months showed diffuse white-matter T2 high signal in the subcortical and periventricular regions. Similar neuroimaging findings have been reported in nine patients with 6p25 deletion syndrome [Chen et al, 2004;Garcia-Cazorla et al, 2004;Caluseriu et al, 2006;van der Knaap et al, 2006;Aldinger et al, 2009] and in three patients with FOXC1 point mutations [Aldinger et al, 2009]. Patient #4 had delayed ossification and bilateral flattening of the proximal femoral epiphyses.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, brain MRI in Patient 4 at 28 months showed diffuse white-matter T2 high signal in the subcortical and periventricular regions. Similar neuroimaging findings have been reported in nine patients with 6p25 deletion syndrome [Chen et al, 2004;Garcia-Cazorla et al, 2004;Caluseriu et al, 2006;van der Knaap et al, 2006;Aldinger et al, 2009] and in three patients with FOXC1 point mutations [Aldinger et al, 2009]. Patient #4 had delayed ossification and bilateral flattening of the proximal femoral epiphyses.…”
Section: Discussionsupporting
confidence: 77%
“…Patients with ARS and the 6p25 deletion syndrome, which includes FOXC1 and other loci, can have psychiatric and neurologic symptoms43-47, although comprehensive brain imaging results are lacking. A recent study found human FOXC1 mutations cause abnormal cerebellar development and meningeal defects48.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter pedigree, heterogeneity in phenotype was also reported, but the clinical severity increased in successive generations. Caluseriu et al described an adult with deletions at 6p25–p24 who had developmental delay, progressive hearing loss, epiphysial dysplasia and abnormal sella turcica, schizophrenia and features of ARS 25. Several reports have noted that ARS can occur in association with failure of the periumbilical skin to involute, resulting in a periumbilical ring or redundant tissue surrounding the umbilicus.…”
Section: Systemic Associationsmentioning
confidence: 99%